Aplikasi E-rapor Perancangan Aplikasi E-rapor Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: SMK Yapan Indonesia) - Virginia Novera; Mochammad Bogoes Saputra Junianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Technology has progressed very rapidly so that information can be accessed quickly. This has changed the pattern of society in various aspects, especially the world of education. SMK Yapan Indonesia has implemented computer technology in data management using Ms. Excel, but the data storage is currently not using an integrated database. In recording grades, teachers still use a manual sistem with paper, and report cards are still taken offline. With a large number of students, this sistem is considered to have a risk so that it can slow down performance in presenting information quickly and precisely. This study aims to design a web-based e-report application that can assist educators in managing grades and facilitating data storage, as well as assisting parents in finding out their children's academic scores quickly and easily. The method used in sistem design is the waterfall method. The design sistem in making e-reports uses the PHP programming language and the Laravel framework and MySQL in database management. At the final stage of the design, software testing is carried out using black box and white box methods. The conclusion of this research report is that a web-based e-report sistem can provide academic information faster with effective and integrated data management and storage.